Herbal Periodontology: A Review - Donde, Rutuja; Shah, Rohit; Mitra, Dipika; Rodrigues, Silvia; Shetty, Gaurav; Prithyani, Saurabh; Vijayakar, Harshad (International Journal For Research In Health Sciences And Nursing, 2018)
Since ancient times, herbs have been used for the treatment of various diseases. Additionally, medicinal herbs have their own traditional values in different tribes. Over the last decade herbal medications is turning out to be a popular form of therapy due to their wide spectrum of biological and medicinal activities, natural ingredients, lower costs, and higher safety margin. There are number of traditional herbal remedies for the treatment and management of diseases related to the oral cavity. The aim of the present article is to review the use of traditional herbal medicines in the management of periodontal diseases.